2020
DOI: 10.59265/mycoasia.2020-03
|View full text |Cite
|
Sign up to set email alerts
|

The genera of Coelomycetes, including genera of lichen forming, sexual morphs and synasexual morphs with coelomycetous morphs (genera A–C)

Abstract: Identification, classification and nomenclature of asexual fungi (including coelomycetes) have been changing rapidly. However, nomenclatural changes of coelomycetous fungi have not been thoroughly discussed since Sutton (1977). Hence, it is essential to compile all scattered data and revisit the list of generic names. In this study, we compiled all published generic names of coelomycetous taxa including invalid and illegitimate names. Further, sexual genera which have coelomycetous asexual morphs are also prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
(359 reference statements)
0
1
0
Order By: Relevance
“…This excludes spores or fungal DNA from a terrestrial origin found in a freshwater habitat.During a survey of freshwater fungi on submerged wood in southern Australia, a coelomycete resembling Hongkongmyces and a Dictyochaeta-like hyphomycete species were found. Coelomycetous fungi are often found in freshwater habitats and occur throughout the ascomycota (Wijayawardene et al, 2020). Dictyohaeta and similar genera are found in the Chaetosphaeriaceae.…”
mentioning
confidence: 99%
“…This excludes spores or fungal DNA from a terrestrial origin found in a freshwater habitat.During a survey of freshwater fungi on submerged wood in southern Australia, a coelomycete resembling Hongkongmyces and a Dictyochaeta-like hyphomycete species were found. Coelomycetous fungi are often found in freshwater habitats and occur throughout the ascomycota (Wijayawardene et al, 2020). Dictyohaeta and similar genera are found in the Chaetosphaeriaceae.…”
mentioning
confidence: 99%